NUMERICAL INVESTIGATION OF THE OCCURRENCE OF A CONCENTRATION-POLARIZATION LAYER - Manatbayev, R.K.; Kalassov, N.B.; Amankeldi, L.B. (KU Publ., 2021)
This work describes the appearance of a concentration polarizing boundary layer on the membrane surface during the separation of the H2/CO2 gas mixture. Concentration polarization occurs when the rejection solution accumulates near the surface of the membrane, forming a boundary layer. The inclusion of concentration polarization effects in the processing of porous walls creates additional difficulties. The boundary layer formed by concentration polarization can be considered as a type of a second porous wall with a lower permeability than the membrane. The main difficulty in modeling this situation is to determine the appropriate boundary conditions for the concentration on the wall, since the concentrations on the wall will constantly change, and the wall geometry itself may change over time due to particle deposition. To account for this effect, a numerical approach was developed, which is discussed in this work.
Keywords: membrane; gas separation; concentration polarization; boundary layer